The effect of PMRI assisted by augmented reality on circle for students’ problem-solving ability - Wulandari, Trisna; Susanti, Ely; Hiltrimartin, Cecil (Jurnal Gantang, 2025)
Mathematical problem-solving ability among students remains low in conventional learning environments. The integration of Augmented Reality (AR) into the Indonesian Realistic Mathematics Education (PMRI) approach facilitates visualization of abstract concepts and promotes contextual learning. This study analyzes the effect of PMRI-based circle learning assisted by AR on students' problem-solving abilities. A quantitative approach was employed using a One Group Pretest pretest-posttest design with 35 eleventh-grade students from SMA Srijaya Negara Palembang. Data were collected through a mathematical problem-solving test based on Polya's four stages: understanding the problem, devising a plan, carrying out the plan, and looking back, administered before and after the intervention. The Shapiro–Wilk test indicated that the data were normally distributed (pretest = 0.084; posttest = 0.309, both > 0.05). Paired sample t-test analysis revealed a pretest mean score of 19.37 and a posttest mean score of 66.51, with a mean difference of 47.14. The t-test result (t = -23.053, Sig. (2-tailed) < 0.001) indicated a significant difference between pretest and posttest scores. These findings demonstrate that the PMRI-based learning design assisted by AR is effective in improving students' problem-solving abilities through contextual learning experiences and interactive visualization. The results suggest that integrating PMRI with Augmented Reality in circle learning represents an effective instructional innovation for enhancing students' problem-solving abilities.